2014
DOI: 10.1371/journal.pone.0112998
|View full text |Cite
|
Sign up to set email alerts
|

Variability among the Most Rapidly Evolving Plastid Genomic Regions is Lineage-Specific: Implications of Pairwise Genome Comparisons in Pyrus (Rosaceae) and Other Angiosperms for Marker Choice

Abstract: Plastid genomes exhibit different levels of variability in their sequences, depending on the respective kinds of genomic regions. Genes are usually more conserved while noncoding introns and spacers evolve at a faster pace. While a set of about thirty maximum variable noncoding genomic regions has been suggested to provide universally promising phylogenetic markers throughout angiosperms, applications often require several regions to be sequenced for many individuals. Our project aims to illuminate evolutionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 58 publications
8
31
0
Order By: Relevance
“…Furthermore, atpE, clpP, rps2, rps3, rps7, rps8, rps11, rpl2, rpl12, rpl20, and cemA genes were evolutionary constraint in Poaceae, especially rps7 and rpl2 genes are almost identical in Poaceae, while psaA, psbC, psbD, petB, and rbcL genes are fast evolved in Poaceae, suggested that chloroplast genomes has been suggested to be lineage specific in some regions, which is consistent with previous studies [44][45][46].…”
Section: Phylogenetic Analysissupporting
confidence: 89%
“…Furthermore, atpE, clpP, rps2, rps3, rps7, rps8, rps11, rpl2, rpl12, rpl20, and cemA genes were evolutionary constraint in Poaceae, especially rps7 and rpl2 genes are almost identical in Poaceae, while psaA, psbC, psbD, petB, and rbcL genes are fast evolved in Poaceae, suggested that chloroplast genomes has been suggested to be lineage specific in some regions, which is consistent with previous studies [44][45][46].…”
Section: Phylogenetic Analysissupporting
confidence: 89%
“…2). These results agree with the high heterogeneity in molecular evolutionary rates in plants (Korotkova et al, 2014; Shaw et al, 2014); however, they also suggest that lineage-specific variation in cpDNA seems to be more accentuated than in nuclear DNA. Furthermore, these data indicate that rate heterogeneity in cpDNA evolution appears to increase in early stages of population differentiation (Duchene and Bromham, 2013; Bromham et al, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…Inversions are difficult to analyze because they are not well recognized in the alignment, especially in small sample sizes (Borsch and Quandt, 2009). Recent studies have discovered that this mutation is usually common in noncoding regions (Borsch and Quandt, 2009), even at population level or in lineage-specific analyses (Quandt et al, 2003; Borsch and Quandt, 2009; Korotkova et al, 2014). Inversions are usually associated with inverted repeat sequences, yielding a hairpin secondary structure such as predicted in our sampling ().…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations